World Cup 2010: South African economic perspectives and policy challenges informed by the experience of Germany 2006 - Stan du Plessis; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
The paper provides a first ex post analysis of the financial burden and economic benefits of the World Cup in Germany 2006. On the usual cost-benefit measures, the experience of WC 2006 appears to be in line with existing empirical work on large sporting events and sport stadia which rarely identify significant net economic benefits. The paper also argues that the event benefit or feel-good factor of sport events should no longer be neglected in cost-benefit studies of large sporting events, even though these effects are likely to be underestimated ex ante due to their possible experience good character. These lessons from Germany 2006 provide a context for analysing the potential risks and benefits for South Africa, the World Cup hosts in 2010. The paper aims to open a discussion on policy decisions, often at the level of urban planning and architecture, that might improve the balance of costs and benefits for sport events and stadia. To that end the paper attempts to initiate a discussion on the economic effects of iconic buildings.
Keywords: 330; Sportereignis; Kosten-Nutzen-Analyse; Prestige; Deutschland; Südafrika